An empirical investigation of time‐varying cost‐effectiveness across the product life cycle. (21st February 2020) - Stevens, Warren; Incerti, Devin; Peneva, Desi; Shrestha, Anshu; Smith, Gregory; Ramaswamy, Krishnan
ABSTRACT: Cost‐effectiveness is traditionally treated as a static estimate driven by clinical trial efficacy and drug price at launch. Prior studies suggest that cost‐effectiveness varies over the drug's lifetime. We examined the impact of "learning by doing, " one of the least studied drivers of changes in cost‐effectiveness across the product life cycle. We combined time‐series trends in effectiveness over time by cancer regimen using the Surveillance, Epidemiology, and End Results‐Medicare database. We estimated the time‐varying effects of treatments in colorectal and pancreatic cancer over their life cycle, including FOLFOX (leucovorin, 5‐fluorouracil, and oxaliplatin) and gemcitabine, on survival of patients. Mean prices over time by strength and dosage form were calculated using historical wholesale acquisition costs. We found consistent downward trends in the mortality hazard ratios, which suggest that effectiveness improves over time. In the case of first‐line FOLFOX for colorectal cancer, the implied incremental cost‐effectiveness ratio based on the observational data fell from $610, 000 per life year gained in 2004 to $27, 000 per life year gained in 2011. Cost‐effectiveness estimated at launch is unlikely to be representative of cost‐effectiveness over the drug's lifetime. In the drugs studied, the impact of time‐varying clinical effectiveness dominated the impact of changing prices overtime.